The Relationship between Anthropometrics and Performance among Collegiate Rodeo Athletes - Colin G. Pennington; Andrew Wolfe; Jared Conely (CV. FOUNDAE, 2023)
Due to a limited number of informative articles available on collegiate rodeo and its athletes, this work aimed to examine the relationship between anthropometric measurements and the physical fitness of rodeo athletes to add to the limited literature focused on the physical profile of rodeo athletes. Within the protocol of university IRB guidelines, 14 (20.86 ± 1.17 years; 178.2 ± 7.85 cm; 86.48 ± 21.39 Kg) male rodeo athletes at a division I school located in the Southwest United States participated in two consecutive six-week resistance training programs. Anthropometric data and fitness performance data from each participating athlete were gathered. The following data were collected: body fat percentage, lean body mass (LBM), vertical jump height, T-test, 300-yard shuttle times, barbell back squat, bench press, trap bar deadlift one repetition maximums (1RMs), single-hand reaction time, and multi-hand reaction time. Research methods included exploratory analysis - including means and standard deviations - to enable a correlational analysis. Descriptive data analysis revealed that the trap bar deadlift 1RM had a significant relationship with the bench press 1RM (r=0.874, p=0.005) and back squat 1RM (r=0.938, p=0.002). Due to limited experience performing resistance training, 1RM performances were possibly based on increased neuromuscular efficiencies – i.e., a 'learning effect.' This study offers new and unique information about the modern rodeo athlete, which can help exercise science practitioners design more efficient training programs.